2009
DOI: 10.1002/gcc.20741
|View full text |Cite
|
Sign up to set email alerts
|

Focal 9p instability in hematologic neoplasias revealed by comparative genomic hybridization and single‐nucleotide polymorphism microarray analyses

Abstract: Copy number losses in chromosome arm 9p are well-known aberrations in malignancies, including leukemias. The CDKN2A gene is suggested to play a key role in these aberrations. In this study overviewing 9p losses in hematologic neoplasias, we introduce the term focal 9p instability to indicate multiple areas of copy number loss or homozygous loss within a larger heterozygous one in 9p. We have used microarray comparative genomic hybridization to study patients with acute lymphoblastic leukemia (ALL, n = 140), ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 31 publications
0
27
0
1
Order By: Relevance
“…32 Furthermore, homozygous loss of the miR-31-encoding genomic locus has been described in human urothelial carcinoma 33 and acute lymphoblastic lymphoma. 34 On the other hand, several studies showed that miR-31 is upregulated in colorectal cancer, hepatocellular cancer and most squamous cell carcinomas. To date, considerable evidence has revealed the important roles of miR-31 in cancer, but whether this miRNA functions as a tumor suppressor or an oncogene differs according to cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…32 Furthermore, homozygous loss of the miR-31-encoding genomic locus has been described in human urothelial carcinoma 33 and acute lymphoblastic lymphoma. 34 On the other hand, several studies showed that miR-31 is upregulated in colorectal cancer, hepatocellular cancer and most squamous cell carcinomas. To date, considerable evidence has revealed the important roles of miR-31 in cancer, but whether this miRNA functions as a tumor suppressor or an oncogene differs according to cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Deletions of p16/INK4A, p14/ARF, and p15/INK4B have been shown to frequently occur in all lymphoid malignancies (10)(11)(12)(13)(14), with homozygous deletions as the most frequent mechanism of inactivation (15). However, despite their high frequency, the prognostic importance of 9p21 alterations is still controversial in ALL (10,16).…”
Section: Introductionmentioning
confidence: 99%
“…PAR1 deletions are frequently observed in patients who are positive for IKZF1 deletion (40). High expressions of miR-24 and miR-542 in patients who are positive for PAR1 deletion were detected.…”
Section: Discussionmentioning
confidence: 92%
“…This miRNA may positively regulate tumor protein 53 (p53) activity (39). The homozygous loss of the miR-31 gene is described in 9p instability in ALL (40). The 9p instability is detected in 19% of patients with ALL, and always includes the homozygous loss of CDKN2A along with loss of CDKN2B, which are associated with BCR/ABL1 and IKZF1 dysfunction (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%